Perancangan Soto Dandori Spare Parts System dan Hydraulic Tools untuk Reduce MTTR dan Efesiensi Man Power - Widya, Adi Rusdi; Rahardjo, Sugeng Budi (DPPM UNIVERSITAS PELITA BANGSA, 2021)
The design and development in maintenance systems and machine maintenance in the manufacturing industry is still required to ensure that production processes are not disrupted and hamper established businesses. The maintenance system created and implemented is able to provide an alternative as a treatment that can reduce the cost of using the spars machine and can be an efficient and low cost system. Dandory system provides ready parts when replacing damaged machine components, so that machine repair time is faster in replacement, the use of tools made in replacing machine components can reduce and avoid potential accidents at work, so that the system used can reduce manpower and repair time, the result of design and development of tools as well as the use of dandory system can reduce the MTTR value by 52% and the use of manpower while repairing the engine is 1 man power.